Moving the mandible in orthognathic surgery – A multicenter analysis. Issue 5 (May 2016) - Thiele, Oliver C.; Kreppel, Matthias; Bittermann, Gido; Bonitz, Lars; Desmedt, Maria; Dittes, Carsten; Dörre, Annegret; Dunsche, Anton; Eckert, Alexander W.; Ehrenfeld, Michael; Fleiner, Bernd; Frerich, Bernhard; et al.
Abstract: Orthognathic surgery has always been a classical focus of maxillofacial surgery. Since more than 100 years, various surgical techniques for mandibular repositioning have been developed and clinically tested. Since the establishment of plate and screw osteosynthesis, orthognathic surgery became more stable and safe. Nowadays, different surgical methods for mobilising the mandible are existing. This international multicenter analysis (n = 51 hospitals) is providing first evidence based data for the current use of different surgical methods. The dominating techniques were Obwegeser/dal Pont (61%) followed by Hunsuck/Epker (37%) and Perthes/Schlössmann (29%). The main osteosynthesis materials were plates (82%), bicortical screws (23.5%), or a combination of both (5.9%). 47% of all centers reported to use several surgical methods at the same time, depending on the anatomical problem and the surgeon's preference. This shows that different surgical methods seem to work as comparable, safe, and reliable procedures in everydays clinical practise. On this basis, further prospective studies could evaluate possible advantages for our patients.